Case report: A case study on the treatment using icaritin soft capsules in combination with lenvatinib achieving impressive PR and stage reduction in unresectable locally progressive pancreatic cancer and a literature review - Liu, Xiaolong; Yang, Feimin; Jia, Dunmao; Dong, Xinyu; Zhang, Yizhuo; Wu, Zhengrong (Frontiers in Genetics, 2023)
Background: Pancreatic cancer is one of the most deadly malignancies in the world. It is characterized by rapid progression and a very poor prognosis. The five-year survival rate of pancreatic cancer in China is only 7.2%, which is the lowest among all cancers and the use of combined paclitaxel albumin, capecitabine, and digital has been the clinical standard treatment for advanced pancreatic cancer since 1997. Also, the application of multidrug combinations is often limited by the toxicity of chemotherapy. Therefore, there is an urgent need for a more appropriate and less toxic treatment modality for pancreatic cancer. Case presentation: The patient was a 79-year-old woman, admitted to the hospital with a diagnosis of unresectable locally advanced pancreatic cancer (T3N0M0, stage IIA), with its imaging showing overgrowth of SMV involvement and unresectable reconstruction of the posterior vein after evaluation. As the patient refused chemotherapy, lenvatinib (8 mg/time, qd) and icaritin soft capsules (three tablets/time, bid) were recommended according to our past experience and a few clinical research cases. The tumor lesion was greatly reduced by 57.5% after the treatment, and the extent of vascular involvement also decreased. The aforementioned medication resulted in a significant downstaging of the patient’s tumor. Conclusion: Better results were achieved in the treatment with icaritin soft capsules and lenvatinib in this case. Because of its less toxic effect on the liver and kidney and bone marrow suppression, it was suitable to combine icaritin soft capsules with targeted drugs for treating intermediate and advanced malignancies, which brings hope to patients who cannot or refuse to take chemotherapy.